Perbedaan Jenis Pertanyaan Netral dengan Jenis Pertanyaan Misleading terhadap Munculnya False Memory pada Anak Usia Prasekolah - M. Apriandi; Charyna Ayu Rizkyanti; Andi Tenri faradiba (Fakultas Psikologi Universitas Pancasila, 2017)
False memory refers to the experience of thinking when we remember something that actually did not really happen. The major problem with false memory is the possibility to make someone may easily be led through misinformation. The current research assessed the difference between two types of question on preschoolers' false memory. This study used an experimental design with 76 participants of preschoolers (53.9% male and 46.1% female, 5-6 years old) who divided into two experimental groups. First group was given a neutral question, while the second group was given a misleading question. In this experiment, the participants were instructed to watch a video, then, one recognition test will be held immediately. In recognition test, participants were showed some pictures and questions about one event. The chi-square analysis shows that there is a significant difference between two types of question (0.04<0.05) the value of Chi-Square was 11.647. Based on these results, it implies that misleading questions might raise more false memory than neutral questions.